IN REGARDS TO THE QUESTION OF SELF-STUDYING FIELD WORK - Vasko, L.V.; Kiptenko, L.I.; Grincova, N.B.; Gortinska, E.N. (World of Medicine and Biology, 2015)
Discussions regarding different aspects of self-studying outside of the classroom for “Histology, cytology and embriology” students. Long-term and short – term types of homework as well as research works are being passed in review. The advantage of utilization of digital microscopic slides for student’s self-studying.